The Influence of Product Quality and Price on Purchase Decisions with Brand Image as a Mediating Variable (A Survey on Local Patrobas Shoe Users Among Gen-Z in Sukabumi City) - Danendra, Rafi; Jhoansyah, Dicky; Komariah, Kokom (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the influence of product quality and price on purchase decisions with brand image as a mediating variable among Patrobas shoe users in the Gen-Z demographic in Sukabumi. A quantitative approach was used with SEM-PLS analysis involving 200 respondents. The results indicate that product quality and brand image significantly affect purchase decisions, while price does not have a direct effect. However, brand image mediates the influence of product quality and price on purchase decisions. The findings provide strategic recommendations for companies to enhance brand image and product quality perception